PRELIMINARY STUDY ON THE EFFECT OF WATERMELON JUICE AND MILK SOLUTION ON DE-ADHESION, DEVELOPMENTAL STAGES AND HATCHING RATE OF EGGS AND SURVIVAL OF FRY OF CLARIAS GARIEPINUS - Salisu, Abba; Umar, Bashir Ibrahim; Usman, Amina Umar; Muhammad, Murtala Namadiana; Yakubu, Mubarak Sani; Yusuf, Fatima Maitama (FUDMA JOURNAL OF SCIENCES, 2021)
Sticky layer of Clarias gariepinus eggs cause the clumping of eggs immediately after fertilization, this create low oxygen, and increase pathogenic infection, thereby reducing fertilization and hatching rate hence reduces in mass production of C. gariepinus seed. Although various substances are use in the removal of the sticky layer, no information is available about the use of watermelon. Therefore, the present study, aim in exploring the potential of using watermelon in removing the sticky layer of C. gariepinus to enhance production. Fertilized eggs were treated with watermelon juice (T1) for comparison with 14 g L-1 milk solution (T2 as de-adhesion reference) and water as control (T0 as adhesion reference). The treatments were agitated with aeration for 30 minutes, rinsed with water, and poured on respective netted hatching trough, with water recirculation for incubation at 27 0C for 24 h period. Except for T0, no clumping of eggs was observed in the remaining groups. Slight variation in attaining a developmental stage among eggs was observed in eggs treated with watermelon. Hatching and survival rate in T2 are higher than T1 and T0 (P<0.05). However, watermelon indicated the potential, as it removed the sticky layer while maintaining hatching and survival rate as in the control (T0) (P>0.05), more should be explored before adoption of watermelon for de-adhesion and incubation of C. gariepinus eggs.